2019
DOI: 10.1002/gcc.22801
|View full text |Cite
|
Sign up to set email alerts
|

A novel RBMX‐TFE3 gene fusion in a highly aggressive pediatric renal perivascular epithelioid cell tumor

Abstract: We report an Xp11 translocation perivascular epithelioid cell tumor (PEComa) with a novel RBMX-TFE3 gene fusion, resulting from a paracentric X chromosome inversion, inv(X)(p11;q26). The neoplasm occurred in an otherwise healthy 12-year-old boy who presented with a large left renal mass with extension into the inferior vena cava.The patient was found to have multiple pulmonary metastases at diagnosis and died of disease 3 months later. The morphology (epithelioid clear cells with alveolar and nested architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…The other examined cells did not meet the break-apart cutoff values, but several cells displayed one co-localization signal and one small separation of the 5 0 TFE3 and 3 0 TFE3 probes ( Figure 2B). Similar subtle break-apart patterns have been described in tumors harboring TFE3 inversions rather than translocations [12,13,14].…”
Section: Tfe3 Activation In a Tsc1-altered Malignant Pecomasupporting
confidence: 73%
“…The other examined cells did not meet the break-apart cutoff values, but several cells displayed one co-localization signal and one small separation of the 5 0 TFE3 and 3 0 TFE3 probes ( Figure 2B). Similar subtle break-apart patterns have been described in tumors harboring TFE3 inversions rather than translocations [12,13,14].…”
Section: Tfe3 Activation In a Tsc1-altered Malignant Pecomasupporting
confidence: 73%
“…This patient died of disease 7 months after surgery [52]. Argani et al [15] also reported a highly aggressive Xp11 mesenchymal neoplasm bearing a novel RBMX partner. These clinical malignant reports combined with the outcome analysis in our study cohort clearly demonstrate that survival for patients with melanotic Xp11 neoplasm is significantly worse than that for patients with Xp11 translocation RCC, which is similar to clear cell RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, fewer than 40 similar cases have been reported in the literature, chiefly in the form of case reports or small series [2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Indeed, it has been identified that these neoplasms share similar clinicopathologic characteristics (younger patients and female predominance), morphology (alveolar architecture and purely epithelioid clear cell morphology), immunoprofile (PAX8 negative, cathepsin K positive, HMB45/Melan-A positive) and oncogenic activation of TFE3 gene fusions (SFPQ is the most common fusion partner; lack of TSC1 or TSC2 gene alterations [27]), suggesting that they belong to a single clinicopathologic spectrum and notably differ from conventional PEComa [5,15]. On the basis of these findings, we and others have proposed the term 'melanotic Xp11 neoplasm' or 'Xp11 neoplasm with melanocytic differentiation' to designate this unique entity, rather than the originally proposed term 'Xp11 translocation PEComa' [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent series of 31 malignant PEComas subjected to DNA and RNA profiling, 5 (16%) tumors harbored a TFE3 fusion, but were wildtype for TSC1 , TSC2 , and FLCN 79 . Other fusion partners that have been detected include NONO , 79,85‐87 RBMX , 88 PRCC , 79,89 RBM10 , 79 and ZC3H4 , 79 but overall SFPQ/PSF appears to be the most recurring gene associated with TFE3 ‐rearranged PEComas 90 …”
Section: Molecular Featuresmentioning
confidence: 92%